Increasing students' love of reading - O'Connell, Cadi (My University, 2013)
Learning to read is exciting, challenging, and sometimes difficult for young students. The literacy skills developed early in a child's education are essential for future success. Students who love to read are self-motivated to pick up a book and become part of the book, but some students do not have an inherent love for reading. It is important that teachers find ways to motivate children to live, love and learn through reading since it is an essential part of life. Teachers are always trying to motivate children who are reluctant readers to fall in love with reading. In order to help children fall in love with reading the researcher carefully prepared literacy activities to motivate children to read and love it. This action research focuses on implementing a joy of reading curriculum to influence students' attitudes toward reading. The author of this study feels that teachers can help to engage and motivate children along with their families to read and love it. The study measured the feedback from parent and student perspectives while conducting different classroom and at home reading activities. The research shows an increase in reading engagement during classroom activities that engage and motivate children to read.
Plan B Paper. 2013. Master of Science in Education- Reading--University of Wisconsin-River Falls. Teacher Education Department. 22 leaves. Includes bibliographical references (leaf 22).
Keywords: Reading (Elementary); School children--Books and reading; Motivation in education